(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study analyzes the influence of the subjective norms, perceived behavioral control, self-efficacy, personal attitudes, and entrepreneurship education on the emergence of entrepreneurial intentions among Surabaya city students. The research used a quantitative method with cross-sectional data. The research used a quantitative method with cross-sectional data. The data was collected through primary sources. Primary data was collected through a questionnaire which was distributed online via a Google form. The questionnaire was filled out by 224 active students studying in the city of Surabaya. SmartPLS 3 was used to process the data analysis using interval analysis levels. The findings revealed that Entrepreneurial Intention (EI) was impacted by Personal Attitude (PA), Self-Efficacy (SE), and Subjective Norm (SN). While Perceived Behavioral Control (PBC) and Entrepreneurship Education (EE) do not affect Entrepreneurial Intention (EI), it is evident from the study’s findings that other variables can have a significant impact on entrepreneurial aspirations. Thus, the government should not solely prioritize entrepreneurship education but should also consider other factors to foster the emergence of entrepreneurial intentions.